Design Of Standard Sop Table Set Up At Poliwangi Jinggo Educational Hotel - Anisa, Nurul; Rachma Amalia , Firda; Wanda Febrian , Ayu (SEAN Institute, 2024)
The hotel industry plays an important role as a supporting sector in the tourism sector. The tourism sector is one aspect that can be utilized to develop the potential of each region. Standard Operating Procedures (SOP) are documents that contain the steps/systems of work in an organization. The purpose of this research is to create a recapitulation of standard SOP table documents that are prepared in written and structured manner know the process of designing the standard SOP for table set up at the Poliwangi Jinggo Education hotel and know the implementation of the waiter's SOP in implementing the table set up standard at the Poliwangi Jinggo Education hotel. The research method used is a qualitative approach, Preparation of service SOP documents is carried out using the error analysis method (GAP) where the preparation of SOP documents is carried out in accordance with ideal conditions and by comparing the existing conditions with the standard set up procedure table at the Poliwangi Jinggo Education hotel. Then, to ensure that the standard SOP document table produced is in accordance with the company's needs, a verification and validation stage is carried out regarding the SOP document created. The results of this research are the Standard Table Set Up SOP. It is hoped that this SOP can become a document for the Poliwangi Jinggo Education Hotel and can also become a reference and guide in handling Table Set Up.